2000
DOI: 10.1186/bcr65
|View full text |Cite
|
Sign up to set email alerts
|

Metalloproteinases: role in breast carcinogenesis, invasion and metastasis

Abstract: The matrix metalloproteinases (MMPs) are a family of zinc-dependent endopeptidases. Their primary function is degradation of proteins in the extracellular matrix. Currently, at least 19 members of this family are known to exist. Based on substrate specificity and domain organization, the MMPs can be loosely divided into four main groups: the interstitial collagenases, gelatinases, stromelysins and membrane-type MMPs. Recent data from model systems suggest that MMPs are involved in breast cancer initiation, inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
425
0
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(455 citation statements)
references
References 44 publications
9
425
0
6
Order By: Relevance
“…Dotted lines indicate the upper limit of healthy controls (95th percentiles); the percentages represent the proportion of patients with values above the upper limit of healthy controls at baseline and at follow-up. Duffy et al, 2000). MMP-9 has been found to be associated with poor prognosis and metastatic potential of breast carcinoma (Duffy et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dotted lines indicate the upper limit of healthy controls (95th percentiles); the percentages represent the proportion of patients with values above the upper limit of healthy controls at baseline and at follow-up. Duffy et al, 2000). MMP-9 has been found to be associated with poor prognosis and metastatic potential of breast carcinoma (Duffy et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of MMPs have been found associated with basement membrane invasion, which plays an important role in metastasis formation (Kalebic et al, 1983;Stetler-Stevenson, 1994, 1995Kleiner and Stetler-Stevenson, 1999). The activity of MMPs is regulated by tissue inhibitors (TIMPs) (Chenard et al, 1996;Duffy et al, 2000;Hirvonen et al, 2003). Among the different MMPs, it has been shown that increased expression of MMP-2 was associated with early relapse and short survival (TalvensaariMattila et al, 1998;Talvensaari-Mattila et al, 1999).…”
mentioning
confidence: 99%
“…Immunoreactivity for MMP-2 was correlated significantly with Masaoka clinical stage, and MMP-2 expression was correlated with the degree of malignant behavior of the thymoma and may be an indicator for distinguishing invasive thymoma from noninvasive thymoma. MMP-2 protein reportedly is correlated with poor prognostic variables in a variety of malignancies, such as breast, 15,16 lung, 17,18 stomach, 19 and head and neck carcinomas. 20 It was long been believed that TIMPs suppressed tumor invasion by inhibiting MMPs in experimental and clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Gelatinases A (MMP-2) and B (MMP-9) can both degrade type IV collagen of basement membranes, the first barrier for cancer invasion. Consistent with their role in breast cancer progression, high levels of MMP-2 have been found to correlate with a poor prognosis in breast cancer patients (Talvensaari-Mattila et al, 1998;Duffy et al, 2000). These MMPs may also play a role in tumour vascularisation.…”
mentioning
confidence: 91%